Mesophilic Anaerobic Co-digestion of Olive-Mill Waste With Cattle Manure: Effects of Mixture Ratio - Rubio, José A.; Romero, Luis I.; Wilkie, Ann C.; García-Morales, José L. (Frontiers in Sustainable Food Systems, 2019)
The co-digestion of agri-food by-products and livestock manure is a feasible alternative for waste management and the recovery of biogas provides an option to generate renewable energy. A series of batch experiments were carried out in order to investigate the mesophilic anaerobic co-digestion of two-phase olive-mill waste (2POMW) and cattle manure (CM) in different mixtures (2POMW:CM = 50:50; 60:40; 75:25; 85:15). In addition, the biodegradability of the co-substrates was studied in order to analyze the performance of the co-digestion process. The results obtained in this study indicate that 2POMW has a low biodegradability since a high soluble organic matter concentration and a low accumulated methane production were obtained at the end of the corresponding biodegradability test. However, CM is more easily biodegradable in mesophilic anaerobic conditions. The co-digestion of both wastes produced an enhancement of the hydrolytic-acidogenic phase, increasing the organic matter potentially bioavailable as volatile fatty acids (VFAs) and the biogas productivity, as a consequence of the subsequent degradation of VFAs by methanogens. However, an accumulation of VFA, principally propionic acid, was observed in the reactors with higher proportions of 2POMW. The volatile solids (VS) removal increased with the 2POMW percentage of the mixture up to 75% fresh weight. The increase of 2POMW above 75% led to a decrease in total VS removal. Moreover, a decrease in methane production was observed for the 85:15 mixture, as a consequence of the high concentration of propionic acid, which is a known inhibitor of methanogenesis. The maximum cumulative methane production and methane yield were achieved in the 75:25 mixture with values of 18.70 L and 112.40 LCH4/kgVSadded, respectively. Compared with 2POMW, the co-digestion produced an increase of 264–319% in the volume of accumulated methane (L), 293–351% in the methane yield (LCH4/kgVSadded) and 312–342% based on the VS consumed (LCH4/kgVSremoved). These results suggest that the mixture of these agro-industrial by-products could be effective to enhance biogas production and organic matter removal from 2POMW.